High-strength wood-plastic composite material and preparation method thereof

By using polystyrene grafted polyethyleneimine and nano-inorganic fillers in wood-plastic composites, the interfacial compatibility and dispersion of the material are improved, and the problem of low mechanical properties of wood-plastic composites is solved, and the load capacity and Antibacterial properties extend service life.

CN119307112APending Publication Date: 2025-01-14HUANGSHAN HUASU NEW MATERIAL SCI & TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411551941.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The physical and mechanical properties of wood-plastic composites are generally low and have poor load bearing capacity, which limits their application range.

Method used

Polystyrene grafted polyethyleneimine as a compatibility agent and nano-inorganic filler, the mechanical properties of the material are enhanced by improving the interface compatibility between thermoplastics and wood fiber powder, and the nano-inorganic filler is improved through quaternization treatment. Dispersibility and antibacterial properties.

Benefits of technology

It significantly improves the mechanical strength and load capacity of wood-plastic composite materials, extends service life, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115321610000091
    Figure BDA0005115321610000091
  • Figure BDA0005115321610000111
    Figure BDA0005115321610000111
  • Figure BDA0005115321610000112
    Figure BDA0005115321610000112
Patent Text Reader

Abstract

The invention discloses a high-strength wood-plastic composite material and a preparation method thereof, and belongs to the technical field of wood-plastic composites.The high-strength wood-plastic composite material is prepared from, by mass, 50-80 parts of wood fiber powder, 20-50 parts of thermoplastic plastic, 2-6 parts of compatilizer, 0.5-1 part of lubricant, 0.3-0.6 part of antioxidant and 4-8 parts of reinforcing filler. Wherein the compatilizer is polystyrene grafted polyethyleneimine, and the reinforcing filler is nano inorganic filler. The interface bonding force between the wood fiber powder and the thermoplastic plastic in the system is increased by using the non-polarity of polystyrene and a large number of active groups in polyethyleneimine, and the compatibility of the wood fiber powder and the thermoplastic plastic is improved, so that the mechanical strength of the material is improved. And the nano inorganic filler is adopted for reinforcement, so that internal gaps of the material can be filled, defects are reduced, the mechanical strength of the material is further enhanced, and the loading capacity of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood-plastic composite materials, and particularly relates to a high-strength wood-plastic composite material and a preparation method thereof. Background Art

[0002] Wood-plastic composite materials are low-carbon and environmentally friendly materials. They are made by mixing thermoplastic polymers with waste plant fibers such as wood powder, rice husks, and straw instead of commonly used resin adhesives, and then melt-compounding them. They are then processed by hot pressing, extrusion, injection, and other molding processes to produce a wood-based composite material. Compared with traditional wood materials, wood-plastic composite materials have many advantages, such as low water absorption, not easy to deform and crack, acid and alkali resistance, corrosion resistance, and easy cleaning. They can replace logs, plastics, and aluminum alloys in many fields such as building materials, furniture, and logistics packaging, thereby helping to reduce the consumption of wood resources.

[0003] However, because biomass fibers are polar and thermoplastic polymers are non-polar, the interface compatibility between the two is poor during the melt compounding process, resulting in generally low physical and mechanical properties of the final wood-plastic composites and poor load bearing capacity, which to a certain extent limits the application of wood-plastic composites. Therefore, in order to promote the rapid development of the wood-plastic composite industry, it is of great significance to innovate its processing technology and modify product performance to expand the application range of the material. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength wood-plastic composite material and a preparation method thereof, so as to solve the problem that the physical and mechanical properties of the wood-plastic composite material are generally low and the load bearing capacity is poor.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The present invention provides a high-strength wood-plastic composite material, comprising the following raw materials in parts by weight:

[0007] 50-80 parts of wood fiber powder;

[0008] 20-50 parts of thermoplastics;

[0009] 2 to 6 parts of compatibilizer;

[0010] 0.5-1 part of lubricant;

[0011] 0.3-0.6 parts of antioxidant;

[0012] 4 to 8 parts of reinforcing filler;

[0013] The compatibilizer is polystyrene grafted polyethyleneimine; and the reinforcing filler is a nano inorganic filler.

[0014] Preferably, the nano inorganic filler includes one or more combinations of nano calcium carbonate, nano silicon dioxide, nano titanium dioxide, nano zinc oxide, and nano clay.

[0015] Preferably, the wood fiber powder includes a combination of one or more of wood powder, bamboo powder and crop straw powder.

[0016] More preferably, the crop straw powder includes a combination of one or more of corn straw powder, wheat straw powder, sorghum straw powder and rice straw powder.

[0017] More preferably, the particle size of the wood fiber powder is 40-100 meshes; and the water content of the wood fiber powder is less than 5%.

[0018] Preferably, the thermoplastic comprises a combination of one or more of polyethylene, polypropylene and polyvinyl chloride.

[0019] Preferably, the lubricant includes one or more combinations of oleamide, silicone powder, stearic acid, sodium stearate, zinc stearate, calcium stearate, magnesium stearate, and ethylene bisstearamide.

[0020] Preferably, the antioxidant includes one or more combinations of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant 1098, antioxidant 1024, and antioxidant DLTP.

[0021] By adopting the above technical solution, since wood fiber powder is a polar material and thermoplastic is a non-polar material, the different polarities of the two will result in low mechanical strength of the wood-plastic composite material obtained. Therefore, the present invention adds polystyrene grafted polyethyleneimine as a compatibilizer of the material. Specifically, polystyrene and thermoplastic are both non-polar materials, and the affinity of the two is good; and polyethyleneimine is a polymer with a highly branched structure, and its molecular chain contains a large number of amino active groups, which can form intermolecular hydrogen bonds with the hydroxyl groups in the cellulose molecules in the wood fiber powder, and form ionic bonds with the carboxyl groups in the hemicellulose molecules, so that the compatibilizer can form a transition layer between the thermoplastic and the wood fiber powder, thereby increasing the interface bonding force between the two, improving the compatibility of the two, and thus improving the mechanical properties of the material.

[0022] In addition, polystyrene contains a large number of rigid groups, while the large number of branched structures of polyethyleneimine provide a certain flexibility. This rigid-flexible structure can well balance the mechanical properties of the material, improving the strength of the material while enhancing its toughness. In addition, the branched chains of polyethyleneimine can penetrate into the microporous structure of wood fiber powder, forming a mechanical interlocking effect, enhancing the connection density inside the material, and thus enhancing the mechanical strength of the composite material.

[0023] At the same time, the present invention also adds reinforcing fillers for reinforcement, specifically, the reinforcing fillers are nano inorganic fillers. The ultra-small particle size of the nano inorganic filler makes it have a very high specific surface area and characteristics, can form a close interface bond with the composite material matrix, improve the interface strength of the material, can also fill the gaps between large particles, reduce the generation of internal defects and cracks in the material, and improve the overall strength of the material. And the rigidity characteristics of the nano inorganic filler can help the composite material to withstand external forces more effectively, produce stress concentration effects and cause the surrounding thermoplastic plastic matrix to produce silver streaks, absorb certain energy, hinder crack expansion, and improve the impact strength of the composite material.

[0024] Preferably, the raw materials of polystyrene grafted polyethyleneimine include carboxylated polystyrene and polyethyleneimine in a mass ratio of 1:(0.3-0.5).

[0025] Preferably, polystyrene grafted polyethyleneimine is prepared according to the following method: adding polyethyleneimine to water, stirring to dissolve and adjusting the solution pH to 5-6, then adding an activator, stirring and mixing to obtain a pre-reaction liquid; adding carboxylated polystyrene to water, adding an activator, stirring to react for 1-2 hours, then dropping the pre-reaction liquid, stirring to react at room temperature for 12-15 hours, and washing and drying after the reaction to obtain polystyrene grafted polyethyleneimine.

[0026] Preferably, the activator includes a combination of one or more of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide and N,N′-dicyclohexylcarbodiimide.

[0027] Preferably, the mass ratio of the total amount of the added activator to the carboxylated polystyrene is (0.2-0.3):1; wherein the activator is evenly divided into two portions and added sequentially.

[0028] Preferably, the carboxylated polystyrene is prepared according to the following method:

[0029] The catalyst and monochloroacetic acid are added to styrene, and the mixture is stirred for 30 to 60 minutes under a nitrogen atmosphere. The temperature is then raised to 100 to 120° C., and the mixture is stirred for reaction for 6 to 8 hours. After the reaction is completed, the mixture is washed and dried to obtain carboxylated polystyrene.

[0030] More preferably, the catalyst comprises one or a combination of cuprous bromide, cuprous chloride, ferrous chloride and cuprous iodide; and the molar ratio of the catalyst to styrene is (0.01-0.02):1.

[0031] More preferably, the molar ratio of monochloroacetic acid to styrene is (0.01-0.03):1.

[0032] By adopting the above technical scheme, the present invention adopts carboxylated polystyrene grafted with polyethyleneimine, and the carboxyl groups on the carboxylated polystyrene can undergo amidation reaction with the amino groups on the polyethyleneimine, and under the action of the activator, the reaction process of the carboxyl groups and the amino groups is promoted, thereby increasing the grafting rate of polyethyleneimine on the polystyrene. The grafted polystyrene can be used as a bridging agent between wood fiber powder and thermoplastic plastics to improve the interface compatibility between the two; the introduction of rigid-flexible structure can also further improve the mechanical strength of the composite material.

[0033] Preferably, the nano inorganic filler is quaternized.

[0034] Preferably, the quaternization treatment comprises the following steps: adding the nano inorganic filler to the solvent, adding the halogenated alkyl silane coupling agent after uniform dispersion, adjusting the solution pH to 6-6.5, raising the temperature to 70-80°C, stirring and reacting for 4-6 hours, adding the alkyl tertiary amine compound, refluxing at 70-80°C for 5-6 hours, and finally centrifugally separating, washing and drying to obtain the nano inorganic filler after quaternization treatment.

[0035] Preferably, the solvent includes a combination of one or more of anhydrous ethanol, isopropanol, n-butanol and methanol.

[0036] Preferably, the haloalkylsilane coupling agent includes a combination of one or more of 3-chloropropyltrimethoxysilane, 3-bromopropyltrimethoxysilane, 2-(chloromethoxy)ethyltrimethylsilane and γ-chloropropyltriethoxysilane; the mass ratio of the haloalkylsilane coupling agent to the nano inorganic filler is (0.35-0.5):1.

[0037] Preferably, the alkyl tertiary amine compound includes one or a combination of dodecyl dimethyl tertiary amine, hexadecyl dimethyl tertiary amine, octadecyl dimethyl tertiary amine, and lauryl amide propyl dimethyl tertiary amine; the molar ratio of the alkyl tertiary amine compound to the halogenated alkyl silane coupling agent is (0.9-1.1):1.

[0038] By adopting the above technical solution, the nano inorganic filler has a strong interfacial force, so it can form a close combination with other compounds in the system, but the nano inorganic filler itself will also produce a corresponding attraction, resulting in the appearance of agglomeration, which will in turn affect the mechanical properties of the material. The present invention quaternizes the nano inorganic filler, and the introduction of a hydrophobic segment can improve the dispersibility of the nano inorganic filler in the composite material and reduce the occurrence of agglomeration.

[0039] Specifically, the nano inorganic filler of the present invention is firstly subjected to surface pretreatment by a haloalkylsilane coupling agent during the quaternization treatment, and then reacts and links the long-chain tertiary amine compound to complete the quaternization treatment. The filler is first treated with a silane coupling agent mainly to improve the compatibility between the filler and the matrix material and provide a chemical bridging effect, while the introduction of the alkyl tertiary amine compound can significantly improve the dispersibility of the filler in the system, and after multi-stage modification, the respective shortcomings can be complemented to achieve the best modification effect.

[0040] Furthermore, the characteristics of the nano-inorganic filler itself enable it to interact with the bacterial cell membrane, resulting in damage to the integrity of the cell membrane structure and interference with the metabolic process of microorganisms. Since the wood-plastic composite material contains biomass materials, it is prone to mildew corrosion under certain conditions. The introduction of nano-inorganic fillers can inhibit the reproduction of bacteria to a certain extent, thereby reducing the performance degradation and shortened service life of the wood-plastic composite material caused by mildew. At the same time, the compatibilizer added by the present invention is polystyrene grafted polyethyleneimine, which can destroy the cell membrane, interact with the negative charge on the cell surface, break the cell charge balance, and then can cooperate with the nano-inorganic filler to enhance the antibacterial performance of the material, and the nano-inorganic filler after quaternization treatment has a stronger antibacterial effect, and the interaction improves the strength of the obtained wood-plastic composite material and enhances the antibacterial effect, expands the application range of the wood-plastic composite material, and prolongs the service life of the material.

[0041] In a second aspect, the present invention provides a method for preparing a high-strength wood-plastic composite material, comprising the following process steps: weighing raw materials of corresponding mass fractions, mixing them uniformly, and then subjecting them to extrusion granulation, secondary extrusion molding and cooling and shaping to obtain a high-strength wood-plastic composite material.

[0042] Preferably, the process temperature of extrusion granulation is 140-180°C.

[0043] Beneficial effects of the present invention:

[0044] 1. In the present invention, polystyrene grafted polyethyleneimine is used as a compatibilizer, and the non-polarity of polystyrene and a large number of active groups in polyethyleneimine are used to increase the interfacial bonding force between wood fiber powder and thermoplastic plastics in the system, thereby greatly improving the compatibility between the two. In addition, polystyrene grafted polyethyleneimine has a rigid-flexible structure, which can well balance the toughness and rigidity of the material, thereby improving the mechanical strength of the composite material.

[0045] 2. The present invention also adds nano inorganic fillers for reinforcement, fills the internal voids of the material, reduces the generation of internal defects of the material, enhances the mechanical strength of the material and improves the load capacity of the composite material. After quaternization treatment, the dispersibility of the nano inorganic filler is significantly improved, and it can be evenly dispersed in the pores of the system to achieve a reinforcement effect. In addition, the nano inorganic filler combined with polystyrene grafted polyethyleneimine can improve the antibacterial properties of the composite material, reduce the problem of decreased mechanical strength of the material caused by mildew corrosion, and improve the service life of the composite material. DETAILED DESCRIPTION

[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Preparation Example

[0048] Preparation Example 1: Polystyrene grafted polyethyleneimine

[0049] Preparation Example 1-1, a polystyrene grafted polyethyleneimine, is prepared according to the following method:

[0050] 1 g of cuprous chloride and 2 g of monochloroacetic acid were added to 100 g of styrene, and the mixture was stirred for 40 min under a nitrogen atmosphere. The temperature was then raised to 110° C., and the mixture was stirred for 7 h. After the reaction was completed, the mixture was washed and dried to obtain carboxylated polystyrene.

[0051] Add 40g polyethyleneimine (average molecular weight of 600) to 50mL water, stir to dissolve and adjust the solution pH to 5.5, then add 10g activator, stir and mix to obtain a pre-reaction solution; add 100g carboxylated polystyrene to 250mL water, add 10g activator, stir to react for 1h, then drop the pre-reaction solution, stir to react at room temperature for 12h, wash and dry after the reaction to obtain polystyrene grafted polyethyleneimine. The activator is a mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in a mass ratio of 1:1.

[0052] Preparation Example 1-2, a polystyrene-grafted polyethyleneimine, is different from Preparation Example 1-1 only in that the amount of polyethyleneimine added is 30 g.

[0053] Preparation Example 1-3, a polystyrene-grafted polyethyleneimine, is different from Preparation Example 1-1 only in that the amount of polyethyleneimine added is 50 g.

[0054] Preparation Example 1-4, a polystyrene-grafted polyethyleneimine, is different from Preparation Example 1-1 only in that the amount of polyethyleneimine added is 20 g.

[0055] Preparation Example 1-5, a polystyrene-grafted polyethyleneimine, is different from Preparation Example 1-1 only in that the amount of polyethyleneimine added is 60 g.

[0056] Preparation Example 1-6, a polystyrene, is prepared according to the following method:

[0057] 1 g of cuprous chloride and 2 g of ethyl 2-bromobutyrate were added to 100 g of styrene, and the mixture was stirred for 40 min under a nitrogen atmosphere. The temperature was then raised to 110° C. and the mixture was stirred for 7 h. After the reaction was completed, the mixture was washed and dried to obtain carboxylated polystyrene.

[0058] Preparation Example 2, a nano inorganic filler

[0059] Preparation Example 2-1: A nano inorganic filler is prepared according to the following method:

[0060] Take 10g of nano-silica (average particle size of 7nm) and add it to 250mL of anhydrous ethanol. After uniform dispersion, add 4.5g of γ-chloropropyltriethoxysilane, adjust the pH value of the solution to 6.5, increase the temperature to 80°C, stir and react for 6h, then add 5g of hexadecyldimethyl tertiary amine, reflux at 80°C for 6h, and finally obtain the quaternized nano-inorganic filler by centrifugation, washing and drying.

[0061] Preparation Example 2-2, a nano inorganic filler, is different from Preparation Example 2-1 only in that the added amount of γ-chloropropyltriethoxysilane is 3.5 g and the added amount of hexadecyldimethyl tertiary amine is 4 g.

[0062] Preparation Example 2-3, a nano inorganic filler, is prepared according to the following method:

[0063] Take 10g of nano-silica (average particle size of 7nm) and add it to 250mL of anhydrous ethanol. After uniform dispersion, adjust the pH value of the solution to 6.5, increase the temperature to 80°C, add 5g of hexadecyldimethyl tertiary amine, reflux for 6h, and finally obtain the quaternized nano-inorganic filler by centrifugation, washing and drying.

[0064] Preparation Example 2-4, a nano inorganic filler, is prepared according to the following method:

[0065] Take 10g of nano-silica (average particle size of 7nm) and add it to 250mL of anhydrous ethanol. After uniform dispersion, add 4.5g of γ-chloropropyltriethoxysilane, adjust the pH value of the solution to 6.5, increase the temperature to 80°C, stir the reaction for 6h, and then centrifuge, wash and dry to obtain the nano-inorganic filler treated with the coupling agent.

[0066] Example

[0067] Example 1, a high-strength wood-plastic composite material is prepared according to the following process steps:

[0068] 6 kg of wood powder (average particle size of 80 mesh), 4 kg of polyethylene (melt index of 190 ° C / 2.16 kg conditions of 1.5 g / 10 min), 0.4 kg of polystyrene grafted polyethylene imine prepared in Preparation Example 1-1, 0.08 kg of calcium stearate, 0.05 kg of antioxidant DLTP and 0.6 kg of nano-silicon dioxide (average particle size of 7 nm) were weighed respectively, mixed evenly and then extruded and granulated by an extruder, wherein the extrusion temperature was 165 ° C, and then secondary extrusion molding and cooling were performed to obtain a high-strength wood-plastic composite material.

[0069] Examples 2 to 6 are high-strength wood-plastic composite materials, which differ from Example 1 only in that the raw materials and the raw material ratios are adjusted. The specific formula is shown in Table 1:

[0070] Table 1 Formula table of Example 1 to Example 6

[0071]

[0072] Among them, Examples 1 to 3 and Example 6 all use the polystyrene grafted polyethyleneimine prepared in Preparation Example 1-1, Example 4 uses the polystyrene grafted polyethyleneimine prepared in Preparation Example 1-2, and Example 5 uses the polystyrene grafted polyethyleneimine prepared in Preparation Example 1-3; the nano-inorganic filler used in Examples 1 to 5 is nano-silicon dioxide, and the nano-inorganic filler used in Example 6 is nano-calcium carbonate.

[0073] Example 7, a high-strength wood-plastic composite material, is different from Example 1 only in that the polystyrene grafted polyethyleneimine prepared in Preparation Example 1-1 is replaced by an equal amount of the polystyrene grafted polyethyleneimine prepared in Preparation Example 1-4.

[0074] Example 8 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the polystyrene grafted polyethyleneimine prepared in Preparation Example 1-1 is replaced by an equal amount of polystyrene grafted polyethyleneimine prepared in Preparation Example 1-5.

[0075] Example 9 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the nano-silicon dioxide is replaced by an equal amount of the nano-inorganic filler prepared in Preparation Example 2-1.

[0076] Example 10 is a high-strength wood-plastic composite material, which is different from Example 9 only in that the nano-inorganic filler prepared in Preparation Example 2-1 is replaced by an equal amount of the nano-inorganic filler prepared in Preparation Example 2-2.

[0077] Example 11 is a high-strength wood-plastic composite material, which is different from Example 9 only in that the nano-inorganic filler prepared in Preparation Example 2-1 is replaced by an equal amount of the nano-inorganic filler prepared in Preparation Example 2-3.

[0078] Example 12 is a high-strength wood-plastic composite material, which is different from Example 9 only in that the nano-inorganic filler prepared in Preparation Example 2-1 is replaced by an equal amount of the nano-inorganic filler prepared in Preparation Example 2-4.

[0079] Comparative Example

[0080] Comparative Example 1 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the amount of polystyrene grafted polyethyleneimine prepared in Preparation Example 1-1 added is 0.1 kg.

[0081] Comparative Example 2 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the amount of polystyrene grafted polyethyleneimine prepared in Preparation Example 1-1 added is 0.8 kg.

[0082] Comparative Example 3 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the added amount of nano-silicon dioxide is 0.2 kg.

[0083] Comparative Example 4 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the amount of nano-silicon dioxide added is 1 kg.

[0084] Comparative Example 5 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the polystyrene-grafted polyethyleneimine prepared in Preparation Example 1-1 is replaced by an equal amount of polystyrene prepared in Preparation Example 1-6.

[0085] Comparative Example 6 is a high-strength wood-plastic composite material, which is different from Example 1 only in that an equal amount of maleic anhydride-grafted polyethylene is used to replace the polystyrene-grafted polyethyleneimine prepared in Preparation Example 1-1.

[0086] Comparative Example 7 is a high-strength wood-plastic composite material, which is different from Example 1 only in that no nano-silicon dioxide is added.

[0087] Comparative Example 8 is a high-strength wood-plastic composite material, which is different from Example 1 only in that the polystyrene-grafted polyethyleneimine prepared in Preparation Example 1-1 is not added.

[0088] Performance testing

[0089] 1. Mechanical properties strength test:

[0090] (1) Flexural strength: According to the relevant records in GB / T 9341-2008 “Determination of flexural properties of plastics”, the flexural strength and flexural modulus of the high-strength wood-plastic composite materials obtained in the examples and comparative examples were tested.

[0091] (2) Simple supported beam impact strength: According to the relevant records in GB / T 1043.1-2008 "Determination of simple supported beam impact properties of plastics Part 1: Non-instrumented impact test", the impact strength of the high-strength wood-plastic composite material obtained in Example and Comparative Example 1 was tested.

[0092] The above test results are shown in Table 2.

[0093] 2. Antibacterial performance test: According to the relevant records in GB / T 2591-2003 "Antibacterial performance test method and antibacterial effect of antibacterial plastics", the antibacterial rate of the high-strength wood-plastic composite material obtained in the embodiment and the comparative example was tested, wherein the test bacteria were Staphylococcus aureus and Escherichia coli.

[0094] The test results are shown in Table III.

[0095] Table 2 Mechanical properties strength test results

[0096]

[0097] Table 3 Antibacterial performance test results

[0098]

[0099]

[0100] According to Table 2 and Table 3, in combination with Example 1 and Example 2 to Example 6, it can be seen that the mechanical strength test results of Example 2 to Example 6 are not significantly different from those of Example 1. Compared with Example 1, Example 2 to Example 6 only change the raw materials and raw material ratios within the required range, and the final material properties have no significant changes.

[0101] Combining Example 1, Example 7, Example 8 and Comparative Example 5, it can be seen that the mechanical strengths of Examples 7, Example 8 and Comparative Example 5 are all reduced compared with those of Example 1, and the reduction in Comparative Example 5 is obvious, and the antibacterial properties of Example 7 and Comparative Example 5 are reduced. Examples 7, Example 8 and Comparative Example 5 all change the grafting rate of polystyrene grafted with polyethyleneimine, wherein the content of polyethyleneimine in Example 7 decreases, resulting in a decrease in the polarity of the compatibilizer and a decrease in the interfacial bonding force with the wood fiber powder, thereby reducing the mechanical strength of the composite material. No polyethyleneimine is added in Comparative Example 5, so the strength decreases more significantly, and the antibacterial effect of polyethyleneimine is lacking, and the antibacterial properties of the material are also reduced; the content of polyethyleneimine is increased in Example 8, and the excessive branched structure of polyethyleneimine easily wraps the polystyrene segment, resulting in a decrease in the non-polarity of the compatibilizer, thereby affecting the improvement of the material strength.

[0102] In combination with Example 1, Example 9 to Example 12, it can be seen that the mechanical strength of Example 9 is improved compared with that of Example 1, and the antibacterial performance is also enhanced. Compared with Example 9, there is no obvious difference in the performance of Example 10, and the mechanical strength of Example 11 and Example 12 decreases, and the antibacterial performance of Example 12 also decreases. Compared with Example 1, Example 9 quaternizes the added nano inorganic filler, which improves the dispersibility of the filler in the system, thereby contributing to the improvement of material performance, and the addition of quaternary ammonium salt segments can cooperate with polyethyleneimine to improve the antibacterial performance of the material; Example 10 only changes the raw material range on the basis of Example 9, so it has little effect on the performance. In Example 11, there is no pretreatment with a silane coupling agent, the bonding force between the filler and the tertiary amine compound decreases, and the compatibility of the material decreases, resulting in a decrease in material performance. In Example 12, there is no quaternization treatment, and the reduction of the hydrophobic segment will also affect the dispersibility and compatibility of the filler, and will also lead to a decrease in antibacterial performance.

[0103] Combining Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 8, it can be seen that the mechanical strength of Comparative Example 1, Comparative Example 2 and Comparative Example 8 is reduced compared with Example 1. The amount of compatibilizer added is adjusted in Comparative Example 1, Comparative Example 2 and Comparative Example 8, wherein Comparative Example 1 reduces the amount of compatibilizer added, and the interface compatibility between the wood fiber powder and the thermoplastic plastic decreases, resulting in a decrease in the mechanical strength of the obtained material, while no compatibilizer is added in Comparative Example 8, and the performance decrease is more obvious. In Comparative Example 2, the amount of compatibilizer added is increased, which will cause the branched chain segments of polyethyleneimine to entangle with each other, which is not conducive to the improvement of interface compatibility, thereby resulting in a decrease in mechanical properties.

[0104] Combining Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 7, it can be seen that the mechanical strength of Comparative Example 3, Comparative Example 4 and Comparative Example 7 is reduced compared with Example 1. Comparative Examples 3, Comparative Examples 4 and Comparative Examples 7 adjust the amount of nano inorganic filler added, among which Comparative Example 3 reduces the amount of nano inorganic filler added, the inorganic filler's reinforcing effect on the material decreases, and the corresponding mechanical strength decreases, while Comparative Example 7 does not add nano inorganic filler, and the performance decreases more significantly. Comparative Example 4 increases the amount of nano inorganic filler added, and a large number of nano particles will become more easily agglomerated without special modification treatment, which is not conducive to the improvement of material strength.

[0105] Combining Example 1 and Comparative Example 6, it can be seen that the mechanical strength of Comparative Example 6 is reduced compared with Example 1, and the antibacterial performance is also significantly reduced. In Comparative Example 6, maleic anhydride grafted polyethylene is used to replace polystyrene grafted polyethylene imine. Although the improvement of compatibility can bring a certain strength improvement, the compatibilizer used in the present invention has a rigid-flexible structure and the branched structure of polyethylene imine can also penetrate the gap of wood fiber powder to form a mechanical interlocking effect, which can further enhance the internal connection structure of the material, reduce the generation of defects, and better enhance the mechanical strength of the material.

[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength wood-plastic composite material, characterized in that: Including the following raw materials by mass: 50-80 parts of wood fiber powder; 20-50 parts of thermoplastics; 2 to 6 parts of compatibilizer; 0.5-1 part of lubricant; 0.3-0.6 parts of antioxidant; 4 to 8 parts of reinforcing filler; The compatibilizer is polystyrene grafted polyethyleneimine; and the reinforcing filler is a nano inorganic filler.

2. The high-strength wood-plastic composite material according to claim 1, characterized in that: The raw materials of polystyrene grafted polyethyleneimine include carboxylated polystyrene and polyethyleneimine in a mass ratio of 1: (0.3-0.5).

3. The high-strength wood-plastic composite material according to claim 1, characterized in that: The polystyrene grafted polyethyleneimine is prepared according to the following method: adding polyethyleneimine to water, stirring to dissolve and adjusting the solution pH to 5-6, then adding an activator, stirring and mixing to obtain a pre-reaction liquid; adding carboxylated polystyrene to water, adding an activator, stirring and reacting for 1-2 hours, then dropping the pre-reaction liquid, stirring and reacting at room temperature for 12-15 hours, and washing and drying after the reaction to obtain the polystyrene grafted polyethyleneimine.

4. The high-strength wood-plastic composite material according to claim 3, characterized in that: The activator includes one or more of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide and N,N'-dicyclohexylcarbodiimide.

5. The high-strength wood-plastic composite material according to claim 1, characterized in that: The nano inorganic filler includes one or more combinations of nano calcium carbonate, nano silicon dioxide, nano titanium dioxide, nano zinc oxide and nano clay.

6. The high-strength wood-plastic composite material according to claim 5, characterized in that: The nano inorganic filler is quaternized.

7. The high-strength wood-plastic composite material according to claim 6, characterized in that: The quaternization treatment comprises the following steps: adding the nano inorganic filler to the solvent, adding the halogenated alkyl silane coupling agent after uniform dispersion, adjusting the pH value of the solution to 6-6.5, raising the temperature to 70-80° C., stirring and reacting for 4-6 hours, adding the alkyl tertiary amine compound, refluxing at 70-80° C. for 5-6 hours, and finally centrifugally separating, washing and drying to obtain the nano inorganic filler after quaternization treatment.

8. The high-strength wood-plastic composite material according to claim 1, characterized in that: The wood fiber powder includes one or more combinations of wood powder, bamboo powder and crop straw powder.

9. The high-strength wood-plastic composite material according to claim 1, characterized in that: The thermoplastic comprises one or more combinations of polyethylene, polypropylene and polyvinyl chloride.

10. A method for preparing a high-strength wood-plastic composite material according to any one of claims 1 to 9, characterized in that: The process comprises the following steps: weighing raw materials of corresponding mass parts, mixing them evenly, and then subjecting them to extrusion granulation, secondary extrusion molding and cooling and shaping to obtain a high-strength wood-plastic composite material.

Citation Information

Cited By

  • Environment-friendly composite material as well as preparation method and application thereof

    CN119978839A

  • Calcium carbonate-based agglomerated stone filler and preparation method thereof

    CN120888119A

  • Calcium carbonate-based trass filler and method for its production

    CN120888119B